Efficacy and safety of garadacimab, a factor XIIa inhibitor for hereditary angioedema prevention (VANGUARD): a global, multicentre, randomised, double-blind, placebo-controlled, phase 3 trial. Issue 10382 (1st April 2023) - Craig, Timothy J; Reshef, Avner; Li, H Henry; Jacobs, Joshua S; Bernstein, Jonathan A; Farkas, Henriette; Yang, William H; Stroes, Erik S G; Ohsawa, Isao; Tachdjian, Raffi; Manning, Michael E; Lumry, William R; et al.
Summary: Background: Hereditary angioedema is a rare and potentially life-threatening genetic disease that is associated with kallikrein–kinin system dysregulation. Garadacimab (CSL312), a novel, fully-human monoclonal antibody that inhibits activated factor XII (FXIIa), is being studied for the prevention of hereditary angioedema attacks. The aim of this study was to evaluate the efficacy and safety of once-monthly subcutaneous administrations of garadacimab as prophylaxis for hereditary angioedema. Methods: VANGUARD was a pivotal, multicentre, randomised, double-blind, placebo-controlled, phase 3 trial that recruited patients (aged ≥12 years) with type I or type II hereditary angioedema across seven countries (Canada, Germany, Hungary, Israel, Japan, the Netherlands, and the USA). Eligible patients were randomly assigned (3:2) to receive garadacimab or placebo for 6 months (182 days) by an interactive response technology (IRT) system. Randomisation was stratified by age (≤17 years vs >17 years) and baseline attack rate (1 to <3 attacks per month vs ≥3 attacks per month) for the adult group. The randomisation list and code were kept by the IRT provider during the study, with no access by site staff and funding representatives. All patients and investigational site staff, and representatives from the funder (or their delegates) with direct interaction with the study sites or patients, were masked to treatment assignment in a double-blind fashion. Randomly assigned patients received a 400-mg loading dose of subcutaneous garadacimab as two 200-mg injections or volume-matched placebo on day 1 of the treatment period, followed by five additional self-administered (or caregiver-administered) monthly doses of 200-mg subcutaneous garadacimab or volume-matched placebo. The primary endpoint was the investigator-assessed time-normalised number of hereditary angioedema attacks (number of hereditary angioedema attacks per month) during the 6-month treatment period (day 1 to day 182). Safety was evaluated in patients who received at least one dose of garadacimab or placebo. The study is registered with the EU Clinical Trials Register, 2020-000570-25 and ClinicalTrials.gov, NCT04656418 . Findings: Between Jan 27, 2021, and June 7, 2022, we screened 80 patients, 76 of whom were eligible to enter the run-in period of the study. Of 65 eligible patients with type I or type II hereditary angioedema, 39 were randomly assigned to garadacimab and 26 to placebo. One patient was randomly assigned in error and did not enter the treatment period (no dose of study drug received), resulting in 39 patients assigned to garadacimab and 25 patients assigned to placebo being included. 38 (59%) of 64 participants were female and 26 (41%) were male. 55 (86%) of 64 participants were White, six (9%) were Asian (Japanese), one (2%) was Black or African American, one (2%) was Native Hawaiian or Other Pacific Islander, and one (2%) was listed as other. During the 6-month treatment period (day 1 to day 182), the mean number of investigator-confirmed hereditary angioedema attacks per month was significantly lower in the garadacimab group (0·27, 95% CI 0·05 to 0·49) than in the placebo group (2·01, 1·44 to 2·57; p<0·0001), corresponding to a percentage difference in means of –87% (95% CI –96 to –58; p<0·0001). The median number of hereditary angioedema attacks per month was 0 (IQR 0·00–0·31) for garadacimab and 1·35 (1·00–3·20) for placebo. The most common treatment-emergent adverse events were upper-respiratory tract infections, nasopharyngitis, and headaches. FXIIa inhibition was not associated with an increased risk of bleeding or thromboembolic events. Interpretation: Monthly garadacimab administration significantly reduced hereditary angioedema attacks in patients aged 12 years and older compared with placebo and had a favourable safety profile. Our results support the use of garadacimab as a potential prophylactic therapy for the treatment of hereditary angioedema in adolescents and adults. Funding: CSL Behring.